Inhibition of breast tumor growth by N(G)-nitro-l-arginine methyl ester (l-NAME) is accompanied by activation of fibroblasts - Sciacca, Marianela (2019)
Nitric Oxide (NO) is involved in many physiological and pathological processes. It is generated by a family of NO synthases (NOS), being the inducible isoform, iNOS, responsible for higher amounts of NO. Here, we report that pharmacological inhibition of NO production by L-NAME reduces both viability and MAPK activated signalling pathways in iNOS positive human and murine cancer cell lines. In vivo, using syngeneic models, in parallel with tumor reduction induced by L-NAME, collagen deposition and α-SMA positive stromal cells are observed. This observation takes place only when tumor cells express iNOS. In vitro, L-NAME induces viability and differentiation on fibroblast. Our results reveal that NO inhibition contributes to stimulate proliferation and activation of fibroblasts in parallel with tumor reduction of iNOS positive breast cancer.